2014
DOI: 10.1007/s00167-014-3109-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of magnetic resonance imaging to diagnose superior labrum anterior–posterior tears

Abstract: In our retrospective study of 444 patients, sensitivity, specificity, and accuracy were all lower than previously reported in the literature for diagnosing SLAP lesions. Our data indicated that while MRI could exclude a SLAP lesion (NPV = 95 %), MRI alone was not an accurate clinical tool. MR arthrography had a large number of false-positive readings in this study. We concluded that even with intra-articular contrast, MRI had limitations in the ability to diagnose surgically proven SLAP lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Subsequently, further exclusions were performed by downloading and reviewing the full-text versions of the remaining studies. After a detailed search and selection process, 14 studies [15,17,22,23,[31][32][33][34][35][36][37][38][39][40] involving 1216 patients with labral lesions met the inclusion criteria for the meta-analysis. Table 1 and Table 2 present the main characteristics of the participants and the included studies.…”
Section: Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, further exclusions were performed by downloading and reviewing the full-text versions of the remaining studies. After a detailed search and selection process, 14 studies [15,17,22,23,[31][32][33][34][35][36][37][38][39][40] involving 1216 patients with labral lesions met the inclusion criteria for the meta-analysis. Table 1 and Table 2 present the main characteristics of the participants and the included studies.…”
Section: Selection Processmentioning
confidence: 99%
“…Recently, multiple high-quality studies [14,[21][22][23] were published, most of which used relatively high resolution for CTA and relatively high-field strength magnets and multidimensional imaging for MRI and MRA. Moreover, no studies have compared the diagnostic performance of MRI, D-MRA, I-MRA and CTA using side-by-side analysis in a single study for the detection of labral lesions.…”
Section: Introductionmentioning
confidence: 99%
“…71 MR imaging has also proven to be a useful modality to rule out the diagnosis of a SLAP lesion, but is not an accurate clinical diagnostic tool when utilized alone. 72 …”
Section: Shoulder Injuriesmentioning
confidence: 99%
“…Given the difficulties in reliably classifying SLAP lesions based on arthroscopic videos [8], it is not surprising that physical examination maneuvers [5,18] and MRI findings [21] are reported to be unreliable in correctly diagnosing SLAP lesions. In two systematic reviews of physical examination reliability and validity for diagnostic accuracy of SLAP tears [5,12], the methodologically robust studies determined that Speed's and Yergason's tests (among all maneuvers) showed sensitivity of 32% and 43% and specificity of 79% and 75%, respectively [5,12].…”
Section: Limitationsmentioning
confidence: 99%
“…The confidence interval for likelihood ratios all included 1.0, indicating that Speed's and Yergason's tests could not rule in or rule out a SLAP lesion in comparison to arthroscopy [12]. Studies investigating MRI and MR arthrography in diagnosing SLAP tears have reported sensitivity and specificity ranging from 66% to 98% and 13% to 89%, respectively [6,7,9,20,21,23]. Variation in study design, MRI methods, and lack of reliability among observers likely accounts for such a wide discrepancy [16].…”
Section: Limitationsmentioning
confidence: 99%